PENGARUH LITERASI KEUANGAN DAN MANAJEMEN KEUANGAN TERHADAP TINGKAT KESEJAHTERAAN KEUANGAN PADA RUMAH TANGGA DI DESA CIPATIK KECAMATAN CIHAMPELAS - Risma Hermawanti (Yayasan Insani Mandiri Santani, 2025)
This research was carried out on a group of households domiciled in Cipatik Village. This investigation aims to measure the extent of the influence between Financial Literacy and Financial Management on Financial Welfare, both individually and collectivelyin households in Cipatik Village. The research design used is a descriptive method and an associative method. Households living in Cipatik Village played a role as an analysis unit in this research. The number of samples involved in this research is 98 respondents. The sample withdrawal procedure applied is Probability Sampling. The analytical approach used is multiple linear regression analysis. The questionnaire, along with testing its validity and reliability, functions as a research instrument. The results of the study showed an influence, both partially and simultaneously, on exogenous variables (financial literacy and financial management) on endogenous variables (welfare). In this case, financial literacy has been proven to have a positive and significant influence on financial welfare with a contribution of 13%, and financial management also has a positive and significant influence on financial welfare with a contribution of 12.2%. Overall, the combination of financial literacy and financial management has a positive and significant influence on financial well-being with a total contribution of 25.2%. Consequently, this research emphasizes the importance for households to deepen financial literacy and understanding, as well as maintain and improve financial management practices, in order to achieve improved household financial welfare. Keywords: Financial Literacy and Financial Management on Financial Welfare